Drought effects on the tissue- and cell-specific cytokinin activity in poplar. Issue 1 (1st December 2017) - Paul, Shanty; Wildhagen, Henning; Janz, Dennis; Polle, Andrea
Abstract : Cytokinins are important phytohormones that regulate plant growth. Here we localized cytokinin activities in poplar trees, which are important biomass crops. We demonstrated that even mild drought stress strongly suppresses cytokinin activities in the cambium, the "stem cells" of trees, resulting in loss in productivity and reduced wood formation. Cytokinin activities also decline in the leaf stalks before shedding. Our results identified critical tissues for drought acclimation in the woody biomass crop poplar and provide a basis for selection of climate-smart trees. Abstract: Climate change with increasing periods of drought is expected to reduce the yield of biomass crops such as poplars. To combat yield loss, it is important to better understand the molecular mechanisms that control growth under drought. Here, the goal was to resolve the drought-induced changes of active cytokinins, a main growth hormone in plants, at the tissue level in different cell types and organs of poplars ( Populus × canescens ) in comparison with growth, biomass, leaf shedding, photosynthesis and water potential. Since cytokinin response is mediated by type-A response regulators, ARR5::GUS reporter lines were used to map cytokinin activity histochemically. The expression of PtaRR3 and PtaRR10 was examined in different stem sections. Young leaves showed strong cytokinin activity in the veins and low staining under drought stress, accompanied by diminished leaf expansion. Leaf scars, at positions where drought-shedding occurred, showed strong reduction of cytokinin activity. The pith in the differentiation zone of stem showed high cytokinin activity with distinct, very active parenchymatic cells and enhanced activity close to primary xylem. This pattern was maintained under drought but the cytokinin activity was reduced. Mature phloem parenchymatic cells showed high cytokinin activity and mature wood showed no detectable cytokinin activity. Cytokinin activity in the cambium was apparent as a clear ring, which faded under drought. Xylem-localized cytokinin activities were also mirrored by the relative expression of PtaRR3, whereas PtaRR10 showed developmental but no drought-induced changes. Primary meristems exhibited high cytokinin activity regardless of drought stress, supporting a function of this phytohormone in meristem maintenance, whereas declining cytokinin activities in apical pith tissues and cambium of drought-stressed poplars linked cytokinin in these cell types with the control of primary and secondary growth processes. Changes in cytokinin activity further imply a role in drought avoidance mechanisms of poplars, especially in the reduction of leaf area.